PENGARUH PENGGUNAAN MEDIA AI WRITING TOOLS DALAM PENDEKATAN DEEP LEARNING TERHADAP KETERAMPILAN MENULIS TEKS BERITA DALAM KONTEKS SOSIAL DI FASE F KELAS XI - Junima Silalahi, Laura; Jamaluddin Sitorus, Pontas; Putri Saptari Wulan, Eka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of media useAI Writing Toolsin the approachDeep Learningon the news text writing skills of class XI students at Marisi Private High School, Medan. The study used a quantitative method with a descriptive design.One Group Pretest-Posttest Design. The sample consisted of 30 students selected using the techniquecluster samplingThe instrument used was a news text writing test. The results of the study showed an average score ofpretestof 54.98 (less category) and the average valueposttestof 83.2 (good category). The results of the hypothesis test using the t-test obtained a calculated t value of 21.40 > t table = 2.04 at a significance level of α = 0.05. Thus, the alternative hypothesis (Ha) is accepted, which means there is a significant influence on the use of mediaAI Writing Toolsin the approachDeep Learningon the news text writing skills of class XI students of Marisi Private High School, Medan.